PUBLIC SERVICES IN CRISIS: STRATEGIC APPROACHES FOR SOUTH AFRICAN LOCAL MUNICIPALITIES AMIDST FINANCIAL CONSTRAINTS - Nhlamulo Mabunda N (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
The inability of South African municipalities to meet their financial obligations may have a substantial impact on the delivery of services to the public. The purpose of this research paper is to explore the numerous ways in which financial constraints effect the efficiency, accessibility, and quality of services provided by municipalities to the citizens in South Africa. To achieve the objectives of this paper, the author utilized a variety of resources including existing literature, journals, books, government documents, and internet sources. The research paper gives insights and potential solutions to improve service delivery within the restrictions of limited financial resources by analysing the issues, determining the core causes of those challenges, and making recommendations and conclusion.